Remarks on Aphaeresis: Alain Badiou’s Method of Subtraction between Plato and Aristotle - Tho, Tzuchien (Filozofski vestnik, 2016)
As a contribution to the ongoing research that Alain Badiou has initiated in thinking of philosophy as conditioned by the domains of science, love, art, and politics, domains where truths are produced, the following investigation takes up the key theoretical link that allows Badiou to establish a relationship between philosophy, on the one hand, and the domains of truth on the other. This link is one that Badiou has schematized by the use of the term “subtraction” which, despite its frequent usage in Badiou’s work, has not often been taken up as a term with its proper historical lineage and with its own set of philosophical problems. My aim is to see how the term “subtraction” can serve as a central method in Badiou’s philosophical program by pointing to how its historical context poses challenges to Badiou’s understanding of the role that the traditions of Platonism and Aristotelianism play in his work.